Multiple components are involved in the efficient joining of double stranded DNA breaks in human cell extracts. - Fairman, M P (1992)
We describe a rapid and efficient in vitro system for the rejoining of double stranded breaks in DNA based on extracts of human 293 cells. Using this system as an assay, we have separated the nuclear extract into several components involved in break rejoining. The unfractionated system can convert approx. 100% of the input DNA, linearized with a restriction enzyme, to high molecular weight material at low temperature (17 degrees C), and at the physiological temperature of 37 degrees C we have shown that competing activities in the extract can also act on the DNA template. We present the fractionation of the extract and the partial purification of a novel factor which will stimulate a crude rejoin activity and in addition increases the activity of purified DNA ligase I. We have also partially purified the break joining activity and show that the chromatographic properties do not directly correspond with the three DNA ligases previously described, indicating that the activity observed may not be due to a single enzyme species. By studying the rejoining of double stranded DNA breaks as a biochemical process, we have demonstrated that the efficient joining of such breaks requires factors in addition to DNA ligases.